1992
DOI: 10.1128/jb.174.7.2131-2137.1992
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of 2,7-dichlorodibenzo-p-dioxin by the lignin-degrading basidiomycete Phanerochaete chrysosporium

Abstract: Under secondary metabolic conditions, the white-rot basidiomycete Phanerochaete chrysosporium degraded 2,7-dichlorodibenzo-p-dioxin (I). The pathway for the degradation of I was elucidated by the characterization of fungal metabolites and oxidation products generated by lignin peroxidase (LiP), manganese peroxidase (MnP), and crude intracellular cell-free extracts. The multistep pathway involves the degradation of I and subsequent intermediates by oxidation, reduction, and methylation reactions to yield the ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
156
1
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(164 citation statements)
references
References 54 publications
(80 reference statements)
4
156
1
3
Order By: Relevance
“…Many low molecular weight compounds have been identified which could play a fundamental role in the enzymatic ligninolytic systems of white-rot fungi [104,[107][108][109][110][111]. Lip and MnP can oxidise various lignin compounds and synthetic lignin only in the presence of a cofactor [112][113][114].…”
Section: Low Molecular Weight Compounds Involved In Lignin Degradationmentioning
confidence: 99%
“…Many low molecular weight compounds have been identified which could play a fundamental role in the enzymatic ligninolytic systems of white-rot fungi [104,[107][108][109][110][111]. Lip and MnP can oxidise various lignin compounds and synthetic lignin only in the presence of a cofactor [112][113][114].…”
Section: Low Molecular Weight Compounds Involved In Lignin Degradationmentioning
confidence: 99%
“…Enzyme-generated Mn III is stabilized by dicarboxylic organic acid chelators, such as oxalate (15,25,26 10.1021/bi002104s CCC: $20.00 © xxxx American Chemical Societyenough to diffuse from the enzyme and oxidize terminal phenolic substrates, including lignin (27) and aromatic pollutants (28)(29)(30)(31). Oxidation of nonphenolic lignin substructures by MnP has been proposed to occur via radical mediators (32,33).…”
mentioning
confidence: 99%
“…The biomass accumulation levelled off around day 15 coinciding with the decrease in the MnP activity observed on day 18 in all but the 0 mg control. Studies done in the last 10 years indicated that white rot fungi have the potential to biodegrade the highly toxic PCB and PCB-like (furans and dioxins) group Valli et al, 1992). These studies concentrated on P. chrysosporium as a model organism and lignin peroxidase as model enzyme.…”
Section: Aroclor Biodegradationmentioning
confidence: 99%